Antibacterial effect of Ginger (Zingiber officinale) against Staphylococcus aureus (Mediscope, 2020)
This experimental study was carried out to determine the antibacterial effect of Crude Ginger Extract (CGE) and Ethanolic Ginger Extract (EGE) against standard strain of Staphylococcus aureus in the Department of Pharmacology and Therapeutics with the collaboration of Department of Microbiology, Mymensingh Medical College, Mymensingh from July 2016 to June 2017. The growth of Staphylococcus aureus started to be inhibited from 70% CGE incorporated media and complete inhibition of growth occurred at 100% CGE. In case of Ethanolic Extract, sensitivity was seen against Staphylococcus aureus using disc diffusion method. Zones of inhibition were 8, 13 and 19 mm at 25, 50 and 100 μg/10 μl respectively. The minimum inhibitory concentration (MIC) of EGE was assessed by broth dilution technique. The MIC of EGE was 400 μg/ml against Staphylococcus aureus. From the study it is clearly observed that there is definite antibacterial effect of crude ginger extract (CGE) and ethanolic ginger extract against Staphylococcus aureus. Further studies are required to detect and isolate the active ingredients present in the Ginger extract responsible for antibacterial effect.Mediscope Vol. 7, No. 1: Jan 2020, Page 31-37